RELEVANSI SUSASTRA HINDU DENGAN PENDIDIKAN KARAKTER - I Made Arsa Wiguna (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2017)
This paper aims to present the idea of the relevance of Hindu’s literature with character education which is currently being encouraged to raised up back in the learning process. Education in general and religious education is basically aimed at forming good character. But today there’s a phenomenon of moral degradation among teenagers, although there’s also the others which has a good moral and character. One of the effort that can be choose to support character education is by reviving religious literature. Literature in Indonesia has existed since the entry of Hindu’s influence to the archipelago. Even in the range of X century, King Dharmawangsa Teguh initiated a project known as “mangjawaken byasamata” or to translating to the Java language the teachings of Bhagavan Vyasa. Hindu’s literature nowadays is still well preserved especially in Bali. Bali as the savior of Hindu’s literature and not only protecting literary works but also developed forms of other literary works. Hindu’s literature to support the efforts of the character education is Sarasamuccaya and Canakya Nitisastra. The values in it, is still relevant in today’s life and a valuable asset for character education. Its need to practice and accustom these teachings so that the purpose of education to humanize humans, and to realize humans could be achieved.